The Origin and Biosynthesis of the Benzenoid Moiety of Ubiquinone (Coenzyme Q) in Arabidopsis . Issue 5 (16th May 2014) - Block, Anna; Widhalm, Joshua R.; Fatihi, Abdelhak; Cahoon, Rebecca E.; Wamboldt, Yashitola; Elowsky, Christian; Mackenzie, Sally A.; Cahoon, Edgar B.; Chapple, Clint; Dudareva, Natalia; Basset, Gilles J.
Abstract : This work shows that plants derive the ring of ubiquinone from tyrosine and phenylalanine via two distinct pathways. A trans- cinnamate 4-hydroxylase, a peroxisomal p- coumarate-CoA ligase, and the peroxisomal transporter PXA1 were identified in the phenylalanine branch. Abstract: It is not known how plants make the benzenoid ring of ubiquinone, a vital respiratory cofactor. Here, we demonstrate that Arabidopsis thaliana uses for that purpose two separate biosynthetic branches stemming from phenylalanine and tyrosine. Gene network modeling and characterization of T-DNA mutants indicated that acyl-activating enzyme encoded by At4g19010 contributes to the biosynthesis of ubiquinone specifically from phenylalanine. CoA ligase assays verified that At4g19010 prefers para -coumarate, ferulate, and caffeate as substrates. Feeding experiments demonstrated that the at4g19010 knockout cannot use para -coumarate for ubiquinone biosynthesis and that the supply of 4-hydroxybenzoate, the side-chain shortened version of para -coumarate, can bypass this blockage. Furthermore, a trans -cinnamate 4-hydroxylase mutant, which is impaired in the conversion of trans -cinnamate into para -coumarate, displayed similar defects in ubiquinone biosynthesis to that of the at4g19010 knockout. Green fluorescent protein fusion experiments demonstrated that At4g19010 occurs in peroxisomes, resulting in an elaborate biosynthetic architecture where phenylpropanoid intermediates have to be transported from the cytosol to peroxisomes and then to mitochondria where ubiquinone is assembled. Collectively, these results demonstrate that At4g19010 activates the propyl side chain of para -coumarate for its subsequent β-oxidative shortening. Evidence is shown that the peroxisomal ABCD transporter (PXA1) plays a critical role in this branch.